Gender Mainstreaming through Integrated Farming Systems: Success witnessed under Farmer FIRST project in Uttar Pradesh - Verma, Nisha; Panwar, Azad Singh; Kashyap, Poonam; Prusty, A K; Shamim, M; Jat, C; Nath, Amit; Gautam, U S (Indian Farming, 2022)
The recognition of the need for gender mainstreaming and empowering women by leveraging male and female differences in the area of farming systems management and production leads to improved family nutrition, occupational health of women, children’s education and health, increased labour productivity. The effectiveness and sustainability of gender responsive interventions is crucial for their contribution in attaining the Sustainable Development Goals of gender equality, food security, alleviating poverty. Apart from that equalizing access to farming systems productive resources through eliminating male and female differences facilitates women in achieving more power over their lives which can further change lives of their families and whole communities. Creation of SHGs of women in villages through mobilizing women is the first step towards the pathway of awareness generation to employment to empowerment.